ANALISIS KOMPARATIF ANTARA PENDAPATAN USAHATANI PADI SAWAH SISTEM TABELA DENGAN TAPIN DI DESA AIR TERANG KECAMATAN TILOAN KABUPATEN BUOL - Made Antara (Universitas Tadulako, 2016)
ABSTRACTThis research aimed at determining: (1) the disparity of income between farmers who implement direct seeding and transplanting seeding of wetland rice system in Air Terang village, Tiloan subdistrictof Buol Regency and (2) the feasibility of wetland rice system in Air Terang, Tiloan subdistrict of Buol Regency. The samples drawn was conducted through a census technique for those who practicing the direct seeding and through a random sampling technique for those who practicing the transplanting system with the total number of respondent samples was 66 farmers. The results of this research showed that: (1) the probability value was 0.001 < 0.05 or tcounted = 3,434> ttable at α of 95% suggesting that there was significant differences in the farmers income between both systems in which the average income was IDR 9,431,146.58/ha/planting season for the former and IDR 8,497,927.41 /ha/planting season for the latter, (2) the value of R/C ratio of the direct seeding and transplanting systems were 2.41 and 2.24, respectively, with both systems are feasible to be developed in Air Terang Village, Tiloan Sub District of Buol district.